Deaf-Blind Interpreting: Building on What You Already Know - Karen Petronio (Cadernos de Tradução)
This article focuses on visual considerations and describes the numerous similarities between video interpreting and deaf-blind interpreting. It also looks at linguistic considerations for deaf-blind interpreting and presents research findings showing similarities and differences between ASL and Tactile ASL. Because many interpreters are unfamiliar with tactile communication, there is a section that includes an overview of Tactile ASL. The issues, descriptions, and data presented in this article are based on situations in the United States and involve the use of ASL and Tactile ASL; however, it is highly likely that these discussions and findings also relate to deaf-blind interpreting done in other countries using other sign languages.